Formation of N-nitrosamines during the analysis of municipal secondary biological nutrient removal process effluents by US EPA method 521. (April 2019) - Chuang, Yi-Hsueh; Shabani, Farzaneh; Munoz, Joline; Aflaki, Roshanak; Hammond, Slavica D.; Mitch, William A.
Abstract: US EPA Method 521 employs activated carbon-based solid phase extraction (SPE) cartridges for analyzing N -nitrosamines. The analysis of N -nitrosamines and their chloramine-reactive and ozone-reactive precursors in nitrified municipal secondary effluent revealed the potential for NDMA to form as an artefact during the analysis. As samples passed through the SPE cartridge, the activated carbon mediated the reaction of nitrite with dimethylamine to form NDMA. The reaction was not significant with tertiary amines. Artefactual NDMA formation was important for nitrite concentrations >0.2 mg/L as N in the Biological Nitrogen Removal (BNR) process effluent. However, it is difficult to define a general threshold for nitrite concentrations, because the importance of the reaction also depends on secondary amine concentrations, which are usually poorly characterized. Pre-treatment of samples with sulfamic acid to destroy nitrite mitigated the artefact. This artefact did not affect NDMA analysis in a nitrified effluent from another facility, likely due to low dimethylamine concentrations. This artefact also did not affect the analysis of primary effluent, due to the lack of nitrite, or the analysis of other N -nitrosamines, likely due to the lack of their secondary amine precursors. Because chloramination does not significantly degrade nitrite, this artefact could affect the analysis of chloramine-reactive N -nitrosamine precursors. Because ozonation rapidly degrades nitrite, it should not affect the analysis of ozone-reactive precursors. However, ozonation at 0.8 mg ozone/mg dissolved organic carbon resulted in significant degradation of all N -nitrosamines, even though simultaneous NDMA formation from ozone-reactive precursors resulted in a net increase in NDMA concentration. Highlights: NDMA formed as an artefact from US EPA Method 521 analysis of nitrified wastewater. Activated carbon-based SPE cartridges formed NDMA from nitrite and dimethylamine. Sulfamic acid pre-treatment to remove nitrite prevented the artefact. Ozonation at 0.8 mg O3 /mg DOC significantly degraded nitrosamines.